«Para que el mundo debajo de tanta verdad vea lo que por ficciones admira»: historicidade e maravilha nos poemas épicos em castelhano e português (1566-1588) - Hélio J. S. Alves (Mélanges de la Casa de Velázquez, 2012)
Perhaps the most striking aspect in the earliest stages of Castilian and Portuguese literary production in the 16th century, as observed throughout the history of literary critical and historical writing, is that the poems appear to merit their description as «versified chronicles» and are barely distinguishable from the historical writing of the period other than in the use of metre. And yet the way in which poems, and in some cases prefaces, address that question shows that this historicity merely reflects the means devised by their authors to transform what they relate into wondrous events. At the same time, the rhetoric of historical wonder persuaded readers of the astonishing truth of the events narrated and the lively descriptions of them. Wonder thus became historical and history became a procession of wonders. Therefore, despite appearances, the plots of the epic poems of the time existed in an ontological grey area somewhere between fact and fiction. To develop the theory implicit in this, the author cites the writings of several poets, including the widely-known cases of Camões and Ercilla, but also such little-known poets as Baltasar de Vargas and Hipólito Sanz.